PELAKSANAAN PROGRAM KAMPUS MENGAJAR PERINTIS PADA SEKOLAH DASAR TERDAMPAK PANDEMI COVID-19 - Devi Ayu Rosita; Rini Damayanti (Program Studi PGSD Universitas Flores, 2021)
The Pioneer Teaching Campus is a form of student concern for the education of elementary school students both in villages and cities, who are currently experiencing very uncomfortable conditions due to the pandemic. The purpose of implementing the Perintis Teaching Campus program is to empower students to assist the teaching process at elementary schools around the village / city where they live. The research method used is a qualitative approach with observation techniques. From the observations it can be concluded that the first program implemented, namely training on the adaptation of online learning technology for UPT SDN 59 Gresik students went well. The offline learning process method that will be applied is the use of video media projector technology for student thematic learning, the use of the Quizizz application for student evaluation work, as well as introducing AKSI (Indonesian Student Competency Assessment) and the Learning Module from the Ministry of Education and Culture.